THE EFFECT OF GUIDED IMAGERY THERAPY ON THE LEVEL OF DEPRESSION IN PATIENTS WITH CHRONIC OBSTRUCTIVE LUNG DISEASE - Ningrum, Ika Agitra; Seno, Budhi Hami; Muljanto, Rahaju Budhi (Medika Kartika : Jurnal Kedokteran dan Kesehatan, 2025)
Chronic obstructive pulmonary disease (COPD) is a disease that can lead to morbidity and mortality worldwide. This experimental study aimed to evaluate the effectiveness of guided imagery interventions in COPD patients treated in the Pulmonology Unit of Sebelas Maret University Teaching Hospital, Surakarta. An analytical experimental design with a randomized controlled trial (pre and post test) approach was used. Paired T-test results showed that the intervention group had a p-value < 0.001, indicating a significant change in the Hamilton Depression Rating Scale (HRDS) scores, while the control group had a p-value of 0.578, showing no significant change. It can be concluded that guided imagery effectively decreased HRDS scores in the intervention group compared to the control group; in other words, guided imagery decreased depression levels among COPD patients. Keywords: COPD, guided imagery, HRDS DOI : 10.35990/mk.v8n4.p344-354